Ectopic expression of Arabidopsis glycosyltransferase UGT85A5 enhances salt stress tolerance in tobacco. - Yan-Guo Sun (Public Library of Science (PLoS), 2013)
Abiotic stresses greatly influence plant growth and productivity. While glycosyltransferases are widely distributed in plant kingdom, their biological roles in response to abiotic stresses are largely unknown. In this study, a novel Arabidopsis glycosyltransferase gene UGT85A5 was identified as significantly induced by salt stress. Ectopic expression of UGT85A5 in tobacco enhanced the salt stress tolerance in the transgenic plants. There were higher seed germination rates, better plant growth and less chlorophyll loss in transgenic lines compared to wild type plants under salt stress. This enhanced tolerance of salt stress was correlated with increased accumulations of proline and soluble sugars, but with decreases in malondialdehyde accumulation and Na(+)/K(+) ratio in UGT85A5-expressing tobacco. Furthermore, during salt stress, expression of several carbohydrate metabolism-related genes including those for sucrose synthase, sucrose-phosphate synthase, hexose transporter and a group2 LEA protein were obviously upregulated in UGT85A5-expressing transgenic plants compared with wild type controls. Thus, these findings suggest a specific protective role of this glycosyltransferase against salt stress and provide a genetic engineering strategy to improve salt tolerance of crops.